Point-of-Care Tests for Hepatitis B Are Associated with A Higher Linkage to Care and Lower Cost Compared to Venepuncture Sampling During Outreach Screenings in an Asian Migrant Population. Issue 1 (16th July 2020) - Ho, Erwin; Michielsen, Peter; Van Damme, Pierre; Ieven, Margareta; Veldhuijzen, Irene; Vanwolleghem, Thomas
Background: This study compares venepuncture versus point-of-care (POC) HBsAg tests on screening cost and linkage to care in prospective outreach screenings in an Asian population in three major cities in Belgium between 10/2014 and 5/2018. Methods: Two community outreach screening programs were organised between 10/2014 and 5/2018. The first screening program used venepuncture and serologic testing for HBsAg. In the second program, HBsAg was tested in finger stick blood POC tests. Positive results were confirmed during outpatient visits with serologic testing. Linkage to care was defined as having received specialist care follow-up with at least one abdominal ultrasound within three months of screening. Results: For 575 participating individuals, 571 valid results were obtained, 456 with venepuncture, and 115 using POC testing. Overall HBsAg seroprevalence was 6.8%. Linkage to care was higher when using POC testing compared to venepuncture (86% or n = 6/7 versus 34% or n = 11/32; p = 0.020). The POC screening program was economically more attractive with a total cost of € 1, 461.8 or € 12.7 per person screened compared to € 24, 819 or € 54.0 per person screened when using venepuncture testing. Results and an appointment for specialist care follow-up were given onsite with POC testing, while with venepuncture testing; results were sent within 20–45 days. Conclusion: In an Asian migrant population in Belgium with an HBsAg seroprevalence of 6.8%, HBV screening based on POC tests resulted in lower costs per person screened (76.5% lower), and higher linkage to care (2.5 times).